Heterogeneous Pd-PdO mesoporous film for ammonia electrosynthesis. (17th September 2022) - Zhang, Mei; Cui, Lin; Mao, Qiqi; Wang, Ziqiang; Yu, Hongjie; Xu, You; Li, Xiaonian; Wang, Liang; Wang, Hongjing
Abstract: Exploring cost-effective and highly active electrocatalysts is of great significance for sustainable electrochemical NH3 synthesis. Palladium (Pd)-based catalysts have been unanimously considered as one of the most efficient catalysts for the nitrogen reduction reaction (NRR). Herein, self-supported mesoporous Pd film with partial oxidation on Ni foam (mPd-PdO/NF) was synthesized through the micelle-assisted chemical replacement method coupled with air oxidation under 260 °C, and the mPd-PdO/NF electrocatalyst exhibited superior NRR performance with the maximum values of r NH3 (24.8 mg h −1 mgcat. −1 ) and FE (16.64%) were obtained at −0.1 V, relative to the single counterparts (mPd/NF and mPdO/NF). It is proposed that both metallic Pd and its oxide domains when co-existing with a phase boundary between them can facilitate nitrogen activation and hydrogenation, resulting in an enhanced NRR performance. This work provides an inspiring strategy for the rational design of highly active and durable metal–metal–oxide nanoarchitectonics for ammonia electrosynthesis.